Advertising agency - D.E. Visuals (Firm) (Florida : D.E. visuals, 1998)
Discusses various services that advertising agencies perform for their clients. Explains how agencies are commonly organized into four functional areas.
DVD format
Keywords: Advertising agencies; Advertising